A new Oligonychus and description of the female allotype of Oligonychus psidium Estebanes & Baker (Acari, Tetranychidae) from Qualea grandiflora Mart. (Vochysiaceae) in northwestern São Paulo, Brazil - Feres, Reinaldo J.F. [UNESP]; Flechtmann, Carlos H.W. (Sociedade Brasileira de Zoologia, 1995)
Oligonychus longipenis, sp.n. and the female allotype of O. psidium Estebanes & Baker, 1968 from Qualea grandiflora Mart. (Vochysiaceae) is described. The male of O. psidium is redescribed in Northwestern São Paulo (Brazil). This is the first record for 0. psidium in Brazil.
Keywords: Acari; Tetranychidae; Taxonomy